2002
DOI: 10.1021/ja017531n
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Optical and Electrochemical Properties of Porphyrin Dimers Linked by Metal Ions

Abstract: The preparation, isolation, and characterization of several new peripherally functionalized monomeric porphyrins and metalloporphyrins and of porphyrin dimers are described. These dimers are obtained by linking with metal ions two monomeric porphyrins bearing at their periphery an enaminoketone chelate fully conjugated with the aromatic ring. Porphyrin dimers linked by metal ions display large interactions in the ground state as evidenced by their electronic spectra and their electrochemical behavior. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(69 citation statements)
references
References 42 publications
3
65
0
1
Order By: Relevance
“…This reagent was previously used by Callot and co-workers to prepare porphyrins conjugated to enamino ketone and enamino aldehyde functions. [15] Complexes 11 and 12 were obtained in 82 and 90 % yield, respectively (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…This reagent was previously used by Callot and co-workers to prepare porphyrins conjugated to enamino ketone and enamino aldehyde functions. [15] Complexes 11 and 12 were obtained in 82 and 90 % yield, respectively (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Such a strategy would be useful to build porphyrin arrays for the study of molecular wires, which are of current interest. [14] Received: January 22, 2003 [Z50995] .…”
Section: Methodsmentioning
confidence: 99%
“…It is considered likely that the second redox wave of the other porphyrin appears at around 1.05 V and is thus buried in the base current. Richeter et al reported similar electrochemical behavior for a Ni-porphyrin dimer, which is closely bonded on planar through the metal complex 24 . On this basis we suggest that two redox waves based on Por/Por system result from the effect of the close intramolecular through-space interaction between the two porphyrins.…”
Section: Resultsmentioning
confidence: 86%